Sistem Absensi Untuk Pencegahan Manipulasi Data Berbasis Android Menggunakan Metode Waterfall (Studi Kasus Di PT. Ingress Malindo Ventures) - Andri Firmansyah; Fuji Heriyanto (Teknik Informatika, Universitas Pelita Bangsa, 2022)
Employee attendance is something that employees must carry out. Because attendance is useful for several things, namely payroll, incentives, and other sales. And since the Covid-19 Pandemic, Management has given a policy, namely WFH. The attendance system at PT Ingress Malindo Ventures currently still uses paper and pens, that is the problem for HRD to calculate employee sales. An alternative to this problem is an attendance system that utilizes a smartphone, which is an Android-based attendance application. This attendance system uses the Waterfall method and for application testing using Blackbox testing. Keywords: Android Attendance